Astragalar and calcaneal morphology of the middle Eocene primate Anchomomys frontanyensis (Anchomomyini): Implications for early primate evolution. Issue 91 (February 2016) - Marigó, Judit; Roig, Imma; Seiffert, Erik R.; Moyà-Solà, Salvador; Boyer, Doug M.
Abstract: Astragali and calcanei of Anchomomys frontanyensis, a small adapiform from the middle Eocene of Sant Jaume de Frontanyà (Southern Pyrenean basins, northeastern Spain) are described in detail. Though these bones have been known for some time, they have never been carefully analyzed in a context that is comprehensively comparative, quantitative, considers sample variation (astragalus n  = 4; calcaneus n  = 16), and assesses the phylogenetic significance of the material in an explicit cladistic context, as we do here. Though these bones are isolated, regression analyses provide the first formal statistical support for attribution to A. frontanyensis . The astragalus presents features similar to those of the small stem strepsirrhine Djebelemur from the middle Eocene of Tunisia, while the calcaneus more closely resembles those of the basal omomyiform Teilhardina . The new phylogenetic analyses that include Anchomomys ' postcranial and dental data recover anchomomyins outside of the adapiform clade, and closer to djebelemurids, azibiids, and crown strepsirrhines. The small size of A. frontanyensis allows comparison of similarly small adapiforms and omomyiforms (haplorhines) such that observed variation has more straightforward implications for function. Previous studies have demonstrated that distal calcaneal elongation is reflective of leaping proclivity when effects of body mass are appropriately accounted for; in this context, A. frontanyensis has calcaneal elongation suggesting a higher degree of leaping specialization than other adapiforms and even some early omomyiforms. Moreover, comparison to a similarly-sized early adapiform from India, Marcgodinotius (which shows no calcaneal elongation) confirms that high distal calcaneal elongation in A. frontanyensis cannot be simply explained by allometric effects of small size compared to larger adapiform taxa. This pattern is consistent with the idea that significant distal calcaneal elongation evolved at least twice in early euprimates, and that early primate niche space frequently included demands for increased leaping specialization.